Healthy Food Consumer Segmentation for Targeting and Positioning New Product Slimming Jelly - Yustina, Ita; Purwadi, Didik; Khuriyati, Nafis (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
AbstractThis study aims to determine market segments, market targets, and market positioning of slimming jelly using the segmentation analysis on healthy food consumer. The respondents used in this study were the consumers who regularly consume healthy food at least once per week within the last two months. The number of samples is 204 respondents. The consumer segmentation is done based on several variables including demographic aspects, motivation, consumption consistency, social tendencies, and attitudes towards new products. The segmentation analysis is carried out using the K-means non-hierarchical clustering method. The method splits the customers into three significantly different clusters at the 0.05 level, namely the adolescent age segment, which has attention to body shape, the adult segment which focus on body weight control, and the adults' segment which are not interested on body weight control. Based on the principle of selective specialization, the target market for slimming jelly is in clusters 1 and 2, with slimming jelly is positioned as a hunger delaying food that claimed to be high in fiber and low in calories so that it is suitable for health and can be used in diet programs.Keywords: healthy food, positioning, segmentation, slimming food, targeting Abstrak Tujuan penelitian ini adalah menentukan segmen pasar, target pasar, dan positioning produk slimming jelly melalui segmentasi konsumen healthy food. Sampel yang digunakan adalah pengkonsumsi healthy food secara rutin minimal 1 kali per minggu dan terakhir melakukan konsumsi dua bulan yang lalu. Jumlah sampel sebanyak 204 responden. Segmentasi berdasarkan pada variabel dari aspek demografis, motivasi, konsistensi konsumsi, kecenderungan sosial, dan sikap terhadap produk baru. Analisis segmentasi menggunakan metode K-means non hierarchical clustering menghasilkan tiga klaster pasar yang berbeda secara siginifikan pada taraf 0,05, yaitu segmen usia remaja yang memiliki perhatian terhadap bentuk badan, segmen dewasa yang memiliki tujuan manajemen berat badan, dan segmen dewasa yang kurang memiliki motivasi manajemen berat badan. Target pasar slimming jelly berdasarkan prinsip selective specialization adalah pada klaster 1 dan 2 dengan positioning slimming jelly sebagai makanan selingan penunda lapar yang memiliki klaim tinggi serat dan rendah kalori sehingga baik untuk kesehatan dan dapat digunakan untuk membantu program diet.Kata kunci: healthy food, positioning, segmentasi, slimming food, targeting